SISTEM PENDUKUNG KEPUTUSAN EVALUASI KINERJA KARYAWAN UNTUK PROMOSI JABATAN STRUKTURAL PADA BIMBINGAN BELAJAR SCIENCEMASTER MENGGUNAKAN METODE GAP KOMPETENSI (PROFILE MATCHING) - Hidayat, Arif Lukman; Pinandita, Tito (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Problem which often happen in course of assessment of employees performance is subjective decision making, especially if some existing employees have close same ability. Using decision support system it is expected to decrease subjective in decision making. It’s replaced by counting all of criteria to all employees, so that employees with the best ability will chosen. Decision Support System by using Gap analysis is made by considering data and norm human resource development. Gap enumeration process conducted to determine the employees recommendation for promotion base on 3 aspect, that is Intellectual Capacities, Attitude Work and Behavior. The result of this process is employees ranking. It is used as recommendation for decision maker to choose the compatible employees at the empty position. This application is built using Microsoft SQL Server as database and Visual Studio 2010 as tools compiler with C# language. Based on the implementation system result, it was concluded that the use of these applications can help decision making employee’s performance evaluation process for structural promotion in Sciencemaster Course.